Effects of short- and long-term plant functional group removal on alpine meadow community niche - Wei, Jingjing; Zhang, Zhonghua; Ma, Li; Hu, Xue; Ade, Haze; Su, Hongye; Shi, Zhengchen; Li, Honglin; Zhou, Huakun (Frontiers in Plant Science, 2024)
The rapid loss of global biodiversity affects the creation and maintenance of community biodiversity and ecosystem structure and function. Thus, it is insufficient to focus solely on the effects of biodiversity loss on community biodiversity without also considering other impacts such as community assembly, niches, interspecific relationships, community stability, and biodiversityecosystem function. In this study, a 3-and 10-year biodiversity manipulation experiment was conducted in an alpine meadow to examine the effects of the individual plant functional groups (PFGs) removal on the niches of community dominant species by removal of Gramineae, Cyperaceae, legumes and other forbs. The results indicated that PFGs removal led to variation in community niches. The long-term PFGs removal led to a gradual decline in the number of Gramineae and Cyperaceae species in the community. Over time, the niche widths of dominant Gramineae and Cyperaceae species gradually narrowed and the degree of niche overlapping decreased. The number of positively and negatively associated species tended to decrease and increase, respecitively. Reduced species diversity led to significant differences in the niches of the remaining species within the community. Thus, species niche differences, resulting from variation in resource allocation, commonly determined the dynamic construction of species composition within the community.